2008
DOI: 10.1158/1055-9965.epi-07-0607
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Tumor-Associated Markers for Early Detection of Malignant Mesothelioma: An Epidemiologic Study

Abstract: Improved detection methods for diagnosis of asymptomatic malignant mesothelioma (MM) are essential for an early and reliable detection and treatment of this type of neoplastic disease. Thus, focus has been on finding tumor markers in the blood that can be used for noninvasive detection of MM. Ninety-four asbestosexposed subjects defined at high risk, 22 patients with MM, and 54 healthy subjects were recruited for evaluation of the clinical significance of 8-hydroxy-2 ¶-deoxyguanosine (8OHdG) in WBCs and plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…Surgery resulted in a sharp decrease in serum mesothelin while chemotherapy induced no change [67]. A significantly larger series from France confirmed the diagnostic utility of mesothelin [69,70] followed by similar results in series from Italy [71,72] and Netherlands [24]. Globally analysed, the results from these different teams showed that serum mesothelin is a good diagnostic marker with areas under ROC curved around 0.8-0.85.…”
Section: Mesothelinmentioning
confidence: 58%
See 1 more Smart Citation
“…Surgery resulted in a sharp decrease in serum mesothelin while chemotherapy induced no change [67]. A significantly larger series from France confirmed the diagnostic utility of mesothelin [69,70] followed by similar results in series from Italy [71,72] and Netherlands [24]. Globally analysed, the results from these different teams showed that serum mesothelin is a good diagnostic marker with areas under ROC curved around 0.8-0.85.…”
Section: Mesothelinmentioning
confidence: 58%
“…Data from literature shows that in asbestos exposed subjects serum mesothelin is only marginally but not significantly increased over normal unexposed subjects [71] and there seems to be no increase over time [79]. Roe et al showed in a small series of 47 malignant mesothelioma for which they had available at least one serum sample, sampled between 6 months and 30 years before diagnosis that there is no significant elevation of serum mesothelin which could be useful for early mesothelioma diagnosis [80].…”
Section: Mesothelinmentioning
confidence: 99%
“…The resulting sub-group could thereby be subject to a more dedicated medical follow-up (i.e. more frequent diagnostic exams) [32,43].…”
Section: Discussionmentioning
confidence: 99%
“…The term "soluble mesothelin-related peptides" (SMRP) refers to a number of similar proteins deriving from subsequent cleavages of cell-surface precursor. SMRP has been found to be able to discriminate between epithelioid MPM histotype (8), and controls with a high specificity (80-85%), though with less consistent sensitivity (60-90%) (9)(10)(11). Diagnostic performance of SMRP may be influenced by the prevalence of specific genetic polymorphisms within the MSLN gene.…”
Section: Updated Research On Biomarkers For Mpmmentioning
confidence: 99%